from sympy.core.function import (Derivative, diff) from sympy.core.numbers import (Float, I, nan, oo, pi) from sympy.core.relational import Eq from sympy.core.symbol import (Symbol, symbols) from sympy.functions.elementary.piecewise import Piecewise from sympy.functions.special.delta_functions import (DiracDelta, Heaviside) from sympy.functions.special.singularity_functions import SingularityFunction from sympy.series.order import O from sympy.core.expr import unchanged from sympy.core.function import ArgumentIndexError from sympy.testing.pytest import raises x, y, a, n = symbols('x y a n') def test_fdiff(): assert SingularityFunction(x, 4, 5).fdiff() == 5*SingularityFunction(x, 4, 4) assert SingularityFunction(x, 4, -1).fdiff() == SingularityFunction(x, 4, -2) assert SingularityFunction(x, 4, 0).fdiff() == SingularityFunction(x, 4, -1) assert SingularityFunction(y, 6, 2).diff(y) == 2*SingularityFunction(y, 6, 1) assert SingularityFunction(y, -4, -1).diff(y) == SingularityFunction(y, -4, -2) assert SingularityFunction(y, 4, 0).diff(y) == SingularityFunction(y, 4, -1) assert SingularityFunction(y, 4, 0).diff(y, 2) == SingularityFunction(y, 4, -2) n = Symbol('n', positive=True) assert SingularityFunction(x, a, n).fdiff() == n*SingularityFunction(x, a, n - 1) assert SingularityFunction(y, a, n).diff(y) == n*SingularityFunction(y, a, n - 1) expr_in = 4*SingularityFunction(x, a, n) + 3*SingularityFunction(x, a, -1) + -10*SingularityFunction(x, a, 0) expr_out = n*4*SingularityFunction(x, a, n - 1) + 3*SingularityFunction(x, a, -2) - 10*SingularityFunction(x, a, -1) assert diff(expr_in, x) == expr_out assert SingularityFunction(x, -10, 5).diff(evaluate=False) == ( Derivative(SingularityFunction(x, -10, 5), x)) raises(ArgumentIndexError, lambda: SingularityFunction(x, 4, 5).fdiff(2)) def test_eval(): assert SingularityFunction(x, a, n).func == SingularityFunction assert unchanged(SingularityFunction, x, 5, n) assert SingularityFunction(5, 3, 2) == 4 assert SingularityFunction(3, 5, 1) == 0 assert SingularityFunction(3, 3, 0) == 1 assert SingularityFunction(4, 4, -1) is oo assert SingularityFunction(4, 2, -1) == 0 assert SingularityFunction(4, 7, -1) == 0 assert SingularityFunction(5, 6, -2) == 0 assert SingularityFunction(4, 2, -2) == 0 assert SingularityFunction(4, 4, -2) is oo assert (SingularityFunction(6.1, 4, 5)).evalf(5) == Float('40.841', '5') assert SingularityFunction(6.1, pi, 2) == (-pi + 6.1)**2 assert SingularityFunction(x, a, nan) is nan assert SingularityFunction(x, nan, 1) is nan assert SingularityFunction(nan, a, n) is nan raises(ValueError, lambda: SingularityFunction(x, a, I)) raises(ValueError, lambda: SingularityFunction(2*I, I, n)) raises(ValueError, lambda: SingularityFunction(x, a, -3)) def test_leading_term(): l = Symbol('l', positive=True) assert SingularityFunction(x, 3, 2).as_leading_term(x) == 0 assert SingularityFunction(x, -2, 1).as_leading_term(x) == 2 assert SingularityFunction(x, 0, 0).as_leading_term(x) == 1 assert SingularityFunction(x, 0, 0).as_leading_term(x, cdir=-1) == 0 assert SingularityFunction(x, 0, -1).as_leading_term(x) == 0 assert SingularityFunction(x, 0, -2).as_leading_term(x) == 0 assert (SingularityFunction(x + l, 0, 1)/2\ - SingularityFunction(x + l, l/2, 1)\ + SingularityFunction(x + l, l, 1)/2).as_leading_term(x) == -x/2 def test_series(): l = Symbol('l', positive=True) assert SingularityFunction(x, -3, 2).series(x) == x**2 + 6*x + 9 assert SingularityFunction(x, -2, 1).series(x) == x + 2 assert SingularityFunction(x, 0, 0).series(x) == 1 assert SingularityFunction(x, 0, 0).series(x, dir='-') == 0 assert SingularityFunction(x, 0, -1).series(x) == 0 assert SingularityFunction(x, 0, -2).series(x) == 0 assert (SingularityFunction(x + l, 0, 1)/2\ - SingularityFunction(x + l, l/2, 1)\ + SingularityFunction(x + l, l, 1)/2).nseries(x) == -x/2 + O(x**6) def test_rewrite(): assert SingularityFunction(x, 4, 5).rewrite(Piecewise) == ( Piecewise(((x - 4)**5, x - 4 > 0), (0, True))) assert SingularityFunction(x, -10, 0).rewrite(Piecewise) == ( Piecewise((1, x + 10 > 0), (0, True))) assert SingularityFunction(x, 2, -1).rewrite(Piecewise) == ( Piecewise((oo, Eq(x - 2, 0)), (0, True))) assert SingularityFunction(x, 0, -2).rewrite(Piecewise) == ( Piecewise((oo, Eq(x, 0)), (0, True))) n = Symbol('n', nonnegative=True) assert SingularityFunction(x, a, n).rewrite(Piecewise) == ( Piecewise(((x - a)**n, x - a > 0), (0, True))) expr_in = SingularityFunction(x, 4, 5) + SingularityFunction(x, -3, -1) - SingularityFunction(x, 0, -2) expr_out = (x - 4)**5*Heaviside(x - 4) + DiracDelta(x + 3) - DiracDelta(x, 1) assert expr_in.rewrite(Heaviside) == expr_out assert expr_in.rewrite(DiracDelta) == expr_out assert expr_in.rewrite('HeavisideDiracDelta') == expr_out expr_in = SingularityFunction(x, a, n) + SingularityFunction(x, a, -1) - SingularityFunction(x, a, -2) expr_out = (x - a)**n*Heaviside(x - a) + DiracDelta(x - a) + DiracDelta(a - x, 1) assert expr_in.rewrite(Heaviside) == expr_out assert expr_in.rewrite(DiracDelta) == expr_out assert expr_in.rewrite('HeavisideDiracDelta') == expr_out